Dinamika Pembentukan Hukum Nasional Indonesia - Rolib Sitorus; Ricky Banke; Joy Zaman Felix Saragih; Frederick Xaverius Tjipto (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
The implementation of Community Service (PkM) activities as out-of-class learning for the community is carried out in certain fields. Aspects of political life that are directly related to society are the formation of legal regulations that regulate order in society. The formation of Indonesian national law is a process that has continued to develop since independence. This process not only involves legal-formal aspects, but is also influenced by political, social, cultural dynamics, and the challenges of globalization. The legacy of colonial law that is still used today is one of the obstacles in creating a legal system based on the noble values ​​of the nation, Pancasila and customary law. The purpose of this paper is to examine the developing dynamics including the role of legislative, executive, and judicial institutions in formulating legal policies. The analysis is also directed at legal reform efforts carried out in various periods, including the New Order and the reform era, and how civil society pressure has influenced the direction of the formation of national law. The discussion in this paper shows that the success of the formation of national law is highly dependent on the synergy between political will, community participation, and the ability of legal institutions to adapt to changing times. Therefore, an inclusive, progressive, and social justice-based approach is needed so that national law is truly able to answer the needs of society and strengthen the rule of law in Indonesia.